The Use of Cangrelor in the Treatment of a Patient with COVID-19-Associated Acute Coronary Syndrome - S. V. Salo; O. V. Levchyshyna; A. Yu. Gavrylyshyn; A. K. Logutov; A. Yu. Hladun (Ukrainian Journal of Cardiovascular Surgery, 2021)
In December 2019, an outbreak of pneumonia caused by a novel coronavirus occurred in Wuhan, Hubei province, spreading rapidly first throughout China and subsequently across Europe, the United States (US), and the rest of the world. On January 30, 2020, the World Health Organization (WHO) declared the COVID-19 outbreak a public health emergency of international concern, and on March 12, 2020, it was characterized as a pandemic. Patients exposed to this virus named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) frequently present with fever, cough, and shortness of breath within 2 to 14 days after exposure, and then usually develop coronavirus disease (COVID-19)-related pneumonia. Although respiratory symptoms prevail among all clinical manifestations of COVID-19, preliminary studies showed that some patients may develop severe cardiovascular (CV) damage.To date, the COVID-19 pandemic has caused significant changes in the prevalence and pathogenesis of cardiovascular diseases among the population in Ukraine and other countries and has led to a significant increase in mortality in this category of patients. These changes necessitated adjustment of drug treatment in patients with concomitant COVID-19.Conclusions. COVID-19 is a global pandemic with unpredictable consequences due to mutually reinforcing damage to the respiratory and cardiovascular systems. Treatment of acute coronary syndrome on the background of COVID-19 requires a systematic approach involving physicians of various specialties as well as compliance with anti-epidemic mea- sures. Interventional treatment is quite effective in treating patients with COVID-associated acute coronary syndrome.COVID-19 patients on mechanical ventilation should use intravenous P2Y12 receptor blockers or drugs that can be crushed and administered through a nasogastric tube. Cangrelor, an intravenous P2Y12 receptor blocker with fast action and high controllability, enabled to achieve the optimal result of the intervention.